In silico Design of a Quadruplex RNA Aptamer Against Carcinoembryonic Antigen, and Evaluating its Potential as a Drug Delivery Vehicle - Muhamad Alkriz, Muhamad; Joujeh, Dima (Asian Pacific Journal of Cancer Biology, 2024)
Background: Colorectal cancer is the third most common cancer worldwide, with carcinoembryonic antigen (CEA) being a key biomarker for tumor prognostic assessment. This study focused on the in silico development of an RNA aptamer capable of efficiently targeting the CEA biomarker, and evaluating its potential to act as a drug delivery vehicle of chemotherapeutic anticancer drugs. Methods: In this study, five G-quadruplex RNA aptamers were manually designed and docked with the CEA protein. The aptamer sequence with the best docking score was optimized through various mutations, and these mutant sequences underwent drug-aptamer docking using AutoDock vina, followed by further docking experiments with CEA, with and without the drug, using the Hdock server. The best aptamer-drug configuration and the entire (aptamers-drug)-CEA complex were then analyzed using molecular dynamics (MD) simulation. Results: Irinotecan exhibited the highest binding affinity with three mutant sequences compared to 5-FU and Raltitrexed, with the seq 3-5/Irinotecan complex showing the best configuration (score: -11.6). This complex also demonstrated a good binding affinity with the target CEA (HDOCK score: -393.07). Throughout 31.6 ns simulation, the RMSD plot of the (aptamer-drug)-CEA complex showed an average of 8.7 A°. The residues of interacting amino acids had lower RMSF than 1.4 Å, except for the ALA A0 (RMSF:1.74 Å). Rg plot showed minimal fluctuation, which were maintained between 19.2 Å and 20.2 Å. The mean SASA was in the range of 112.8–125.8 nm2. H-bonds were observed with an average of 7.3 hydrogen bonds. MD simulation results indicated that the (aptamers-drug)-CEA complex maintained a stable, low-flexibility, and relatively compact structure throughout the simulation. Conclusion: The study concludes that the designed quadruplex RNA aptamer can potentially target the CEA biomarker with good binding affinity and serves as an effective carrier for Irinotecan. However, in vitro and in vivo experiments are necessary for further validation.